PEMBERIAN ABDOMINAL STRETCHING EXERCISE DAN WILLIAM’S FLEXCION EXERCISE TERHADAP DISMENORE - Andera, Neta Ayu (Stikes Yarsi Mataram, 2024)
Dysmenorrhea complaints experienced by women during menstruation are characterized by lower abdominal cramps, caused by uterine muscle spasms limiting normal activities. Pain interferes with daily activities. One of the non-pharmacological therapies using abdominal stretching exercise and William's flexcion exercise. Objective: Giving abdominal stretching exercise and william's flexcion exercise can reduce nhyeri dysminorea at SMPN Kediri Method: Providing abdominal stretching exercise therapy and william's flexcion exercise. To reduce dysminorea pain to 48 female students at SMPN Kediri. Results: The provision of abdominal stretching exercise intervention and William's flexcion exercise can reduce dysminorea in Kediri Junior High School students and does not cause a similar effect on Kediri Junior High School students. Conclusion: Abdominal stretching exercise and william's flexcion exercise interventions reduce dysmenorrhea intensity. The results of administering abdominal stretching exercises and William’s flexion exercises to adolescents at SMPN Kediri indicate a reduction in dysmenorrhea without causing side effects. The conclusion is that the administration of abdominal stretching exercises and William’s flexion exercises can reduce dysmenorrhea among female students at SMPN Kediri. Therefore, it is recommended that female students apply abdominal stretching exercises and William’s flexion exercises to alleviate dysmenorrhea